Addressing the non-meeting of the productivity target of collectors in Optum 360 - Cajayon, Khadija S. (Animo Repository, 2021)
In this action research, we focused on addressing the limited knowledge and technical skills, which resulted in the issue of non-meeting of the productivity target of the collectors in Optum 360. Competency plays a big part in using knowledge and technical skills in performing tasks. In Business Process Outsourcing, meeting the Service Level Agreement or SLA is key to retaining and possibly getting more business. Limited knowledge and technical skills manifested in the wrong process committed by some collectors. It also contributes to the low performance of employees. This action research aims to improve the timeliness in delivering claims, especially the aging and high-dollar accounts. As well as enhancing the execution and use of existing standard operating procedures or process maps through training will ensure uniformity of actions taken to contribute to easing production. We used different data collection methods such as Team meetings, Informal conversations, Active inquiry, documents, and records. We used Kalamas and Kalamas Gap Analysis, Fisher et al.’s Training Cycle, and ADKAR Model to implement the changes in our department. These interventions produced the expected result, and it increased the knowledge and technical skills of the collectors, which led to the increase in productivity of our department. Doing the action research taught me to immerse myself in the situation of others before jumping to conclusions; it helped me open my eyes and understand what my colleagues need. It improved my relationship with my colleagues and helped build trust and respect. Keywords: training, skills, productivity, competency